2019
DOI: 10.1785/0120190104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Radiated Seismic Energy of Three Aftershocks Sequences at Guerrero, Mexico, Subduction Zone

Abstract: General characteristics of seismic energy release of thrust earthquakes in Mexico have been reviewed in the past; however, a detailed analysis can contribute to a better understanding of the mechanisms that control its distribution along the Guerrero, Mexico, subduction zone. To address it, we obtain the source spectra of the 2012 Mw 7.5 Ometepec‐Pinotepa Nacional, the 2014 Mw 7.2 Papanoa, and the 2018 Mw 7.2 Pinotepa Nacional earthquakes, as well as of their M≥4.0 aftershocks to estimate their seismic moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…11). Even within the same tectonic environment, E R /M 0 has significant variations, as has been reported by Plata-Martínez et al (2019) in the Middle American Trench, where variations in E R /M 0 are associated with heterogeneities along the trench, such as asperities. The different types of earthquakes have differences in the frequency content of the seismic energy released.…”
Section: Discussionsupporting
confidence: 63%
“…11). Even within the same tectonic environment, E R /M 0 has significant variations, as has been reported by Plata-Martínez et al (2019) in the Middle American Trench, where variations in E R /M 0 are associated with heterogeneities along the trench, such as asperities. The different types of earthquakes have differences in the frequency content of the seismic energy released.…”
Section: Discussionsupporting
confidence: 63%
“…Husker et al ( 2018 ) found a high conductivity zone on the upper layer of the subducting slab, which was associated with the presence of highly pressurized fluids as observed in different regions of the globe ( Audet & Kim, 2016 ) and that may explain the migration pattern of tectonic tremor and SSE cycles in that state and globally Warren-Smith et al, 2019 ). In the Ometepec-Pinotepa segment, Plata-Martínez et al ( 2019 ) examined the radiated energy of aftershock sequences of both the 2012 M w 7.5 Ometepec-Pinotepa Nacional ( hereafter 2012 Ometepec earthquake ) and the 2018 M w 7.2 Pinotepa Nacional earthquakes ( hereafter 2018 Pinotepa earthquake ). The ratio between the seismic energy to the seismic moment also suggests the presence of fluids along this zone.…”
Section: Pore Pressure and Fluids In The Ometepec-pinotepa Nacional R...mentioning
confidence: 89%
“…In the Ometepec–Pinotepa segment, Plata‐Martínez et al. (2019) examined the radiated energy of aftershock sequences of both the 2012 M w 7.5 Ometepec–Pinotepa Nacional (hereafter 2012 Ometepec earthquake) and the 2018 M w 7.2 Pinotepa Nacional earthquakes (hereafter 2018 Pinotepa earthquake). The ratio between the seismic energy to the seismic moment also suggests the presence of fluids along this zone.…”
Section: Introductionmentioning
confidence: 99%